2020
DOI: 10.3390/cells9071602
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miR-640 and Zinc Finger Protein 91 (ZFP91) in Angiopoietin-1-Induced In Vitro Angiogenesis

Abstract: Angiopoietin-1 (Ang-1) is a ligand of Tie-2 receptors that promotes angiogenesis. It has been established that regulatory loops exist between angiogenic growth factors and distinct pro or anti-angiogenic miRNAs, but the nature and the roles of Ang-1-regulated miRNAs remain unclear. In this study, we assessed the role of miR-640 in Ang-1-induced angiogenesis in human umbilical vein endothelial cells (HUVECs). Exposure to Ang-1 (300 ng/mL) from 6 to 72 h significantly decreased expression of mature miR-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…These products including sonic hedgehog homolog (SHH) ( Weyers et al, 2020 ), HIF-1 ( Chai et al, 2020 ; Coyle et al, 2020 ), and BMP ( Samee et al, 2008 ; Yang et al, 2021 ), which recruit cells in the vascularization area to secret angiogenic factors. PDGF, angiopoietin 1, and ephrinB2 also show an indirect role on angiogenesis ( Harel et al, 2020 ; Hosaka et al, 2020 ; Yoon et al, 2020 ). They may help to stabilize the newly formed capillaries by recruiting smooth muscle cells.…”
Section: Co-culture System Optimizationmentioning
confidence: 99%
“…These products including sonic hedgehog homolog (SHH) ( Weyers et al, 2020 ), HIF-1 ( Chai et al, 2020 ; Coyle et al, 2020 ), and BMP ( Samee et al, 2008 ; Yang et al, 2021 ), which recruit cells in the vascularization area to secret angiogenic factors. PDGF, angiopoietin 1, and ephrinB2 also show an indirect role on angiogenesis ( Harel et al, 2020 ; Hosaka et al, 2020 ; Yoon et al, 2020 ). They may help to stabilize the newly formed capillaries by recruiting smooth muscle cells.…”
Section: Co-culture System Optimizationmentioning
confidence: 99%
“…Despite the discovery of several miRNAs associated with the development and progression of glioma (16)(17)(18), researchers are yet to investigate the effects of other miRNAs on glioblastoma cells (19)(20)(21). For example, miR-640 inhibits the formation of capillaries (22); however, its role in cancer development has not yet been investigated. In their research, Li et al (23) and Zhai et al (24) both demonstrated that miR-640 exerts tumor-suppressive effects in ovarian cancer and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…There were 43 candidate miRNA targets of circ_0068087 predicted by both databases ( Supplementary Figure 2A ). Among these miRNAs, we screened out five miRNAs that were implicated in AS progression, including miR-186-5p ( 13 ), miR-140-3p ( 20 ), miR-640 ( 21 ), miR-515-5p ( 22 ), and miR-665 ( 23 ). MiR-186-5p was selected for further experiments due to it having the most significant negative regulatory relationship with circ_0068087 ( Supplementary Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%